Unraveling anti-inflammatory components and mechanisms in decoction derived from Allium ascalonicum L. Bulbs and Sojae Semen Praeparatum via UPLC-MS/MS integrated with bioinformatics - Yuanyuan Jiang; Junya Wen; Wenfeng Wei; Jinhai Huo; Yingying Yang; Weiming Wang (CyTA - Journal of Food)
The Cong-Chi decoction (CCD) is composed of Allium ascalonicum L. bulbs and Sojae Semen Praeparatum. Food-based therapy exhibits minimal side effects when compared to the conventional use of antipyretic and analgesic drugs for treating common cold (wind-cold type). However, the current state of research is deficient in exploring the components of CCD, and there is a lack of assessment regarding the fever-reducing and anti-inflammatory mechanisms associated with CCD. This study synergizes Ultra-Performance Liquid Chromatography-Mass Spectrometry/Mass Spectrometry (UPLC-MS/MS) with bioinformatics, validating the anti-inflammatory components of CCD and predicting its anti-inflammatory mechanisms. Our results reveal that UPLC-MS/MS identified 33 components in CCD. Notably, components such as genistein, glycitein, daidzein, scopoletin, and 7-hydroxycoumarin demonstrated a high binding affinity with the core protein Tumor Necrosis Factor-alpha (TNF-α). They inhibited the expression of TNF-α and Interleukin-6 (IL-6) in a Lipopolysaccharide (LPS)-induced inflammation model. Furthermore, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis indicates that anti-inflammatory mechanisms of CCD involve pathways related to cell apoptosis, arginine and proline metabolism, and Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling.